SAT0163 Long Term Treatment with Abatacept or Tocilizumab Does Not Increase Epstein-Barr Virus Load in Patients with Rheumatoid Arthritis. (15th July 2016) - Massy, E.; Muis-Pistor, O.; Martin, M.; Auger, I.; Guzian, M.-C.; Guis, S.; Roudier, J.; Pham, T.; Balandraud, N.
Abstract : Background: Epstein-Barr Virus (EBV) is a widely disseminated lymphotrophic herpes virus implicated in a lot of benign and malignant disorders. In transplant patients, EBV load is enhanced because of immunosuppressive drugs (cyclosporine) and in a few cases, it can lead to lymphoproliferative disorders (LPD). An EBV load higher than 500 copies per 500 ng of DNA is a predictive factor of post transplant lymphoma [1, 2] Similarly, immunity against EBV is particular in RA patients: the level of antibodies against EBV is higher in RA than in healthy controls [3], RA patients have a defective EBV specific supressor T cell function [4].The risk to develop a lymphoma is higher in RA patients than in controls. We have previously shown that: 1/ EBV load is 10 fold higher in RA patients than in controls [5] and 2/ Methotrexate and TNF alpha antagonists (immunosuppressive drugs used in RA patients) do not increase EBV load in RA [6]. Objectives: Here, we monitored EBV load over 3 years in patients with RA treated by 2 more recent biologics, Abatacept (CTLA4 Ig) a T cell activation inhibitor, or Tocilizumab, an anti IL6 receptor antibody. Methods: EBV load in the peripheral blood mononuclear cells (PBMCs) from 55 patients under Abatacept (+/− Methotrexate) and 35 patients under Tocilizumab (+/− Methotrexate) was monitored from 6 months up to 3 years, by real time PCR. The influences of treatment duration and disease activity score 28 (DAS28) index on EBV load were analyzed. Results: Neither Abatacept nor Tocilizumab significantly enhanced EBV load over time. None of our patients developed EBV associated lymphoma. Conclusions: Long term usage of Methotrexate with Abatacept or Tocilizumab in patients with RA does not significantly influence EBV load in PBMCs. References: Baldanti F et al. High levels of Epstein Barr virus DNA in blood of solid organ transplant recipients and their value in predicting postransplant lymphoproliferative disorders. Journal of Clinical Microbiology 38: 613–619, 2000 Morito M, et al. Quantitative analysis of Epstein Barr virus load by using a real time PCR assay. Journal of Clinical Microbiology 37: 132–136, 1999 Alspaugh M et al. Elevated levels of antibodies to Epstein Barr virus antigens in sera and synovial fluids of patients with rheumatoid arthritis. Journal of Clinical Investigation 67: 1134–1140, 1981 Tosato G et al. Defective EBV specific suppressor T cell function in rheumatoid arthritis. New England Journal of Medicine 305: 1238–1243, 1981 Balandraud N et al. Epstein-Barr Virus Load in the peripheral blood of patients with Rheumatoid arthritis. accurate quantification using re[2] Kimura H, al time Polymerase chain reaction. Arthritis and Rheumatism 2003;48:1223–1228. Balandraud N et al. Long-term treatment with methotrexate or tumor necrosis factor alpha inhibitors does not increase epstein-barr virus load in patients with rheumatoid arthritis. Arthritis and Rheumatism 57(5): 762–767, 2007 Acknowledgement: This work was supported by AORC AP-HM, INSERM and Chugai. Disclosure of Interest: E. Massy: None declared, O. Muis-Pistor: None declared, M. Martin: None declared, I. Auger: None declared, M.-C. Guzian: None declared, S. Guis: None declared, J. Roudier: None declared, T. Pham: None declared, N. Balandraud Grant/research support from: This work has been partially supported by Chugai group